THE POTENTIAL OF REMDESIVIR AGAINST SARS COV 2: A REVIEW - B., VINOD; BABU, AMALA; MARIA, FEMY; ANTONY, SNEHA (International Journal of Current Pharmaceutical Research, 2020)
Covid 19, the pandemic originated in the Chinese city of Wuhan, had the entire world conquered. The structure and transmission of the causative organism, Coronavirus is well studied. Remdesivir, the product of Gilead pharmaceuticals, was effective against many viral infections, including Ebola and SARS. It comes under the category of nucleoside prodrug and has given promising results in the early trials against SARS COV 19. In depth, research is taking place at a rapid pace, so that Remdesivir will be available to the therapeutic community as an effective remedy for the pandemic caused by SARS COV2. If this meets success, the darkest era in the modern history of mankind may become a memory in the near future.